"Will Weed for Food": The political economy of organic farm volunteering in Hawai'i. (October 2015) - Mostafanezhad, Mary; Suryanata, Krisnawati; Azizi, Saleh; Milne, Nicole
Highlights: WWOOF emerges within broader trends toward market-based activism. Tensions exist in WWOOF between host farmers' and volunteers' expectations. In spite of the purported ideals, hosts' participation is a short term labor strategy. WWOOF's capacity to enact change is limited by its inherent contradictions. The performative effects of WWOOF support alternative socio-economic discourses. Abstract: Organic farm volunteering programs facilitate opportunities for volunteer tourists to fulfill their desire for authenticity and meaning through farm experience, while simultaneously meeting organic farmers' need for affordable labor. We situate this presumably mutual partnership within the broader expansion of market-based activism and the political economy of organic agriculture in Hawai'i. Drawing on semi-structured interview and survey data from farm hosts and volunteers, we argue that while organic farm volunteering offers a short term coping strategy for some organic farmers, the cultural logic and rationale that propels these programs perpetuates the underlying labor problems that plague small organic farms. As a result, they lack the capacity to ameliorate the structural challenges that participants often set out to oppose. Without losing sight of its performative potential to discursively create space for alternative economic formations, this article demonstrates the limitations of organic farm volunteering when utilized as a form of civic participation to drive economic and socio-environmental change.